Reciprocal Interactions of Mitochondria and the Neuroimmunoendocrine System in Neurodegenerative Disorders: An Important Role for Melatonin Regulation - Polyakova, Victoria O.; Kvetnoy, Igor M.; Anderson, George; Rosati, Jessica; Mazzoccoli, Gianluigi; Linkova, Natalya S. (Frontiers in Physiology, 2018)
Structural and functional alterations of mitochondria are intimately linked to a wide array of medical conditions. Many factors are involved in the regulation of mitochondrial function, including cytokines, chaperones, chemokines, neurosteroids, and ubiquitins. The role of diffusely located cells of the neuroendocrine system, including biogenic amines and peptide hormones, in the management of mitochondrial function, as well as the role of altered mitochondrial function in the regulation of these cells and system, is an area of intense investigation. The current article looks at the interactions among the cells of the neuronal-glia, immune and endocrine systems, namely the diffuse neuroimmunoendocrine system (DNIES), and how DNIES interacts with mitochondrial function. Whilst changes in DNIES can impact on mitochondrial function, local and systemic alterations in mitochondrial function can alter the component systems of DNIES and their interactions. This has etiological, course and treatment implications for a wide range of medical conditions, including neurodegenerative disorders. Available data on the role of melatonin in these interactions, at cellular and system levels, are reviewed, with directions for future research indicated.